Adequate combined therapy of acute rhinitis and sinusitis - A. A. Sedinkin; Y. V. Luchsheva; A. F. Zakharova; G. Y. Tsarapkin (Медицинский совет, 2014)
Nasty days of autumn and winter, with their cold days, windy weather, rain and snow bring about a period of increased morbidity. It's not a secret that almost every cold is accompanied by an inflammatory ENT disease. Along with the wider availability of the Internet in the recent years, an increasing number of patients do not seek medical help but choose self-medication. This leads to frequent and often unjustified administration of antibacterial drugs, growth in the number of antibiotic-resistant strains of microorganisms, which finally results in higher incidence of chronic acute bacterial sinusitis and severe complications. On the other hand, clinical practitioners often "commit a sin" of prescribing a list of medications which do not always constitute a rational therapy, often ignoring the routine patient examination that would ensure accurate diagnosis. The purpose of this article is to recall the clinical pattern, diagnosis and current treatment schemes for acute rhinitis and sinusitis, to help us avoid certain mistakes in the future.